2013
DOI: 10.3233/jad-2012-121630
|View full text |Cite
|
Sign up to set email alerts
|

Altered Levels of Homocysteine and Serum Natural Antioxidants Links Oxidative Damage to Alzheimer's Disease

Abstract: Increasing evidence supports the theory that oxidative stress plays an important role in the pathogenesis of Alzheimer's disease (AD). Homocysteine (Hcy), uric acid (UA), bilirubin, and albumin are simple laboratory parameters that are related to oxidative stress. In this study we compared serum Hcy and antioxidant levels in patients with AD and normal cognitive function. In this cross-sectional study, 143 AD patients and 1,553 patients with normal cognitive function aged 65 years and over were enrolled. Mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 52 publications
3
46
1
2
Order By: Relevance
“…Among those 24 studies, 21 were case-control studies comparing serum uric acid levels in Alzheimer's disease patients with healthy controls [14-24, 28-32, 36-40] and 3 studies were cohort studies assessing risk of Alzheimer's disease in individuals with various categories of serum uric acid levels [33][34][35]. Among those 24 studies, 19 studies were published in English [14][15][16][17][18][19][20][21][22][23][24][28][29][30][31][32][33][34][35] while the other 5 studies were published in Chinese [36][37][38][39][40]. Those 21 case-control studies included a total of 1128 cases of Alzheimer's disease and 2498 controls without Alzheimer's disease [14-24, 28-32, 36-40].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 98%
See 1 more Smart Citation
“…Among those 24 studies, 21 were case-control studies comparing serum uric acid levels in Alzheimer's disease patients with healthy controls [14-24, 28-32, 36-40] and 3 studies were cohort studies assessing risk of Alzheimer's disease in individuals with various categories of serum uric acid levels [33][34][35]. Among those 24 studies, 19 studies were published in English [14][15][16][17][18][19][20][21][22][23][24][28][29][30][31][32][33][34][35] while the other 5 studies were published in Chinese [36][37][38][39][40]. Those 21 case-control studies included a total of 1128 cases of Alzheimer's disease and 2498 controls without Alzheimer's disease [14-24, 28-32, 36-40].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 98%
“…Of the remaining 35 studies, 6 studies were excluded for irrelevant outcomes and 5 studies were excluded for no usable data. Thus, 24 studies were finally included into the meta-analysis [14][15][16][17][18][19][20][21][22][23][24][28][29][30][31][32][33][34][35][36][37][38][39][40]. Among those 24 studies, 21 were case-control studies comparing serum uric acid levels in Alzheimer's disease patients with healthy controls [14-24, 28-32, 36-40] and 3 studies were cohort studies assessing risk of Alzheimer's disease in individuals with various categories of serum uric acid levels [33][34][35].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…In addition, some studies suggest that patients with higher serum UA levels have a markedly lower risk of progressing from impaired cognitive function to dementia [37], [38], while some studies found that even mild elevation of UA might enhance the risk of cognitive decline in older adults [39]. Other study revealed that patients with normal cognitive function have higher serum UA levels than AD patients [40]. Considering these inconsistent possibilities, we tried to establish what consensus could be reached from various studies by examining the change of serum UA levels in AD patients compared to healthy controls with meta-analytic techniques.…”
Section: Introductionmentioning
confidence: 99%
“…This effect manifests through an improvement in oxidative stress and other peripheral markers of dementia that show a significantly better state when both entities are present. [30][31][32][33] In 2009, this hypothesis arose from a basic study that increased our understanding of the protection offered by diabetes against Alzheimer disease. In this study of mature hippocampal neurons, researchers observed that loss of insulin receptors and poor diffusion of related ligands was mitigated and normalised by the action of insulin.…”
Section: Antidiabetic Drugs and Their Link To Alzheimer Diseasementioning
confidence: 98%